2016
DOI: 10.3399/bjgp16x685717
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ethnicity on acceptability of method of blood pressure monitoring: a cross-sectional study in primary care

Abstract: BackgroundAmbulatory and/or home monitoring are recommended in the UK and the US for the diagnosis of hypertension but little is known about their acceptability.AimTo determine the acceptability of different methods of measuring blood pressure to people from different minority ethnic groups.Design and settingCross-sectional study with focus groups in primary care in the West Midlands.MethodPeople of different ethnicities with and without hypertension were assessed for acceptability of clinic, home, and ambulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…In contrast to the fairly consistent views of self-management, women's experiences of doctor-and midwife-led care were more variable, perhaps reflecting the paucity of clinical guidance and evidence that currently underpins postpartum hypertension management (16,17). Some participants reported Themes emerging from previous qualitative work evaluating BP self-management were echoed by this study: confidence with HBPM (9) and preference for self-monitoring (10,18,19). Patients have previously reported HBPM to be more straightforward, time efficient and potentially more accurate in terms of representing their true BP (19).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In contrast to the fairly consistent views of self-management, women's experiences of doctor-and midwife-led care were more variable, perhaps reflecting the paucity of clinical guidance and evidence that currently underpins postpartum hypertension management (16,17). Some participants reported Themes emerging from previous qualitative work evaluating BP self-management were echoed by this study: confidence with HBPM (9) and preference for self-monitoring (10,18,19). Patients have previously reported HBPM to be more straightforward, time efficient and potentially more accurate in terms of representing their true BP (19).…”
Section: Discussionmentioning
confidence: 64%
“…Some participants reported Themes emerging from previous qualitative work evaluating BP self-management were echoed by this study: confidence with HBPM (9) and preference for self-monitoring (10,18,19). Patients have previously reported HBPM to be more straightforward, time efficient and potentially more accurate in terms of representing their true BP (19). Participants in this cohort reported a higher level of confidence when down-titrating medication than has been reported in relation to up-titration of antihypertensive medications, in poorly controlled essential hypertension (9,20).…”
Section: Discussionmentioning
confidence: 73%
“…Themes emerging from previous qualitative work evaluating BP self-management were echoed by this study: confidence with HBPM (9) and preference for self-monitoring (10,18,19). Patients have previously reported HBPM to be more straightforward, time efficient and potentially more accurate in terms of representing their true BP (19).…”
Section: Discussionmentioning
confidence: 71%
“…Outcome studies have demonstrated that on‐treatment HBPM has superior prognostic value than OBP . Advantages of using HBPM are: (1) in treated patients, the phenomena of white‐coat effect and masked uncontrolled hypertension are as common as white‐coat and masked hypertension in untreated patients and can be identified by HBPM or ABPM; (2) HBPM is widely available in many countries and is inexpensive (in fact, patients have decided to cover the cost of the technique themselves); (3) most patients prefer HBPM rather than ABPM for out‐of‐office BP evaluation, particularly for repeated long‐term use, because it causes less discomfort and restriction of daily activities and sleep and (4) this method motivates patients by increasing their awareness and getting them actively involved in their BP monitoring and long‐term control. Several randomized controlled trials have shown that patients with treated hypertension who perform HBPM have improved hypertension control rates, which are caused by improved long‐term adherence to drug therapy .…”
Section: Clinical Relevancementioning
confidence: 99%